Blended Learning as a Contemporary Way towards Effective English Language Teaching: A Critical Review - Sarwat un Nisa Makdoomi (Language Art, 2021)
Blended learning is new but one of the most globally accepted forms of teaching-learning methods. The popularity of this hybrid mode has been proved many a time by the researchers for its useful impact in various fields of studies including English language. This mode has marked its popularity in the field of English language not only because it improves the LSRW skills in learners but also due to its significance in building an interactive, collaborative and motivated learning environment which is often a challenge for English language classes. As, the COVID-19 pandemic has marked the importance of online mode of teaching; the interest towards blended learning has increased many folds. But despite its popularity, there are many loopholes in the system that must be addressed to propagate this hybrid learning mode as a routine in the education system. The current review therefore provides a unique inspection of more than fifty research papers that has by far evaluated various advantages of blended learning system with special reference to English language and has also drafted multifaceted recommendations that will help in making the blended learning a successful alternative for regular face-to-face teaching.